2000
DOI: 10.1054/bjoc.2000.1307
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine plus best supportive care (BSC) vs BSC in inoperable non-small cell lung cancer – a randomized trial with quality of life as the primary outcome

Abstract: Three hundred patients with symptomatic, locally advanced or metastatic NSCLC not requiring immediate radiotherapy were enrolled into this randomized multicentre trial comparing gemcitabine + BSC vs BSC alone. Patients allocated gemcitabine received 1000 mg/m2on days 1, 8 and 15 of a 28-day cycle, for a maximum of six cycles. The main aim of this trial was to compare patient assessment of a predefined subset of commonly reported symptoms (SS14) from the EORTC QLQ-C30 and LC13 scales. The primary end-points wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
157
1
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(167 citation statements)
references
References 20 publications
(14 reference statements)
6
157
1
3
Order By: Relevance
“…Single agent paclitaxel was also demonstrated to produce a 2-month longer MST (6.8 vs 4.8 months) in comparison with supportive care in a randomised trial with no upper limit of age for accrual (Ranson, 2000), and this drug appeared highly attractive for treating elderly patients, in view of the increasing evidence that a weekly schedule may improve its toxicity profile (Alberola et al, 2002). Furthermore, retrospective (Martin et al, 1997;Shepherd et al, 1997) and prospective studies (Altavilla et al, 2000;Anderson et al, 2000;Ricci et al, 2000) have also supported the use of gemcitabine in elderly NSCLC patients, given its good tolerability and activity regardless of age.…”
mentioning
confidence: 99%
“…Single agent paclitaxel was also demonstrated to produce a 2-month longer MST (6.8 vs 4.8 months) in comparison with supportive care in a randomised trial with no upper limit of age for accrual (Ranson, 2000), and this drug appeared highly attractive for treating elderly patients, in view of the increasing evidence that a weekly schedule may improve its toxicity profile (Alberola et al, 2002). Furthermore, retrospective (Martin et al, 1997;Shepherd et al, 1997) and prospective studies (Altavilla et al, 2000;Anderson et al, 2000;Ricci et al, 2000) have also supported the use of gemcitabine in elderly NSCLC patients, given its good tolerability and activity regardless of age.…”
mentioning
confidence: 99%
“…The chemotherapy regimens were single agent gemcitabine, paclitaxel, vinorelbine in a selected elderly population, the combination mitomycin C, ifosfamide and cisplatin (MIC) and single agent docetaxel (Cullen et al, 1999; the Elderly Lung Cancer Vinorelbine Italian Study Group, 1999;Anderson et al, …”
Section: Sirmentioning
confidence: 99%
“…The study reported by Anderson et al (2000) in the August issue of the BJC demonstrated a sustained improvement in symptom score with corresponding improvement in QOL, when gemcitabine (GC) was combined with best supportive care (BSC) vs BSC alone in advanced NSCLC. Although GC produced an objective response rate of 19%, with fewer patients requiring radiotherapy (RT); and the time to RT salvage was longer with GC, there was no difference in survival.…”
Section: Sirmentioning
confidence: 99%
“…Clinical benefit is evidenced from phase III randomized trials showing survival, symptomatic and quality of life benefits (Non-small Cell Lung Cancer Collaborative Group, 1995;Cullen et al, 1999;Anderson et al, 2000). The optimal chemotherapeutic regimen and the magnitude of benefit in day-to-day clinical practice however remains controversial.…”
mentioning
confidence: 99%
“…These have shown an economic advantage for patients treated with chemotherapy over the cost of patients who received supportive care alone (Jaakkimainen et al, 1990;Anderson et al, 2000). More recent work has shown significant differences in the costs associated with different regimens (Berthelot et al, 2000).…”
mentioning
confidence: 99%